Comparison of coffee production in Mexico against the 30 best producing countries - Jiménez Monterrubio, Andrea; Ramirez Sainz, Regina; Zaragoza Ziranda, Juan Manuel; Flégl, Martin (Memorias del Concurso Lasallista de Investigación, Desarrollo e innovación, 2019)
Coffee is considered as a global exporting and importing goods. In total, there are approximately 80 countries producing coffee, where Brazil, as the biggest coffee producer, produces around 6,000 million pounds of coffee every year. In this article, we analyze productivity of the 30 biggest coffee producers based on Data Envelopment Analysis. The results show that Brazil, Vietnam and Colombia are the only 100% efficient countries. The average efficiency of all countries is 22.631% with SD 30.115%. Mexico belongs among the inefficient countries, as its efficiency is 14.907%. With a post-projection analysis, Mexico should increase its production (measured by pounds per year) by 6.69 times or increase the production potential from each hectare.